Effects of diazepam on the behavioral response to stress in nulliparous and primiparous rats - Garcia, C. F. R.; Moreira, A. B.; Zimberknopf, E.; Hucke, E. E. T. S. (Scientific Electronic Archives, 2017)
Reproductive experience (RE), i.e. the conjunct of gestation, parturition and lactation, is associated with alterations in secretions of hormones, reducing, for example, steroids and prolactin, possibly for the rest of a female’s life. Responses to stress are related to a behavioral expression of anxiety in the elevated plus-maze, once stress has an anxiogenic effect in this experimental model; both responses, to stress and anxiety, can be permanently modified in function of the ER. Besides, reduction in seprimiparous females’ sensibility to stress has been demonstrated. In this way, the results obtained until the present moment suggests that stress models the behavioral responses to stress and consequently to reproductive experience and that the hormonal scenery related to the estral cycle phase participates in this modulation. In this way too, the reproductive experience is able to reduce the sensibility to stress; however this fact is also influenced by the estral cycle phase.